2020
DOI: 10.1016/j.eururo.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Magnetic Resonance Imaging, with or Without Magnetic Resonance Imaging-targeted Biopsy, and Systematic Biopsy for Detecting Prostate Cancer: A Cochrane Systematic Review and Meta-analysis

Abstract: Context: Magnetic resonance imaging (MRI), with or without MRI-targeted biopsy (MRI pathway), is an alternative test to systematic transrectal ultrasonography-guided biopsy in men suspected of having prostate cancer. At present, evidence on which test to use is insufficient to inform detailed evidence-based decision making. Objective: To determine the diagnostic accuracy of the index tests MRI only, MRItargeted biopsy, MRI pathway, and systematic biopsy, as compared with templateguided biopsy (reference standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
189
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(224 citation statements)
references
References 39 publications
12
189
1
7
Order By: Relevance
“…Another issue related to the salvage approach is the unclear definition of BCR which should trigger initiation of salvage radiotherapy. Its PSA-value threshold varied from 0.05 to 0.5 in different clinical trials and guidelines [26]. Taken together, optimally, postoperative radiotherapy should be performed in patients who suffer, albeit with possible low PSA values, or in those who are developing BCR with an unmeasurable PSA value at the initiation of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue related to the salvage approach is the unclear definition of BCR which should trigger initiation of salvage radiotherapy. Its PSA-value threshold varied from 0.05 to 0.5 in different clinical trials and guidelines [26]. Taken together, optimally, postoperative radiotherapy should be performed in patients who suffer, albeit with possible low PSA values, or in those who are developing BCR with an unmeasurable PSA value at the initiation of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…While several risk calculators and biomarkers have been developed and are currently under evaluation [2][3][4], the "MRI pathway" is supported by level 1 evidence, but seems to be limited by the low to moderate inter-reader and -center reproducibility and the low specificity/positive predictive value (PPV) [5][6][7]. Studies have shown that omitting biopsies in patients with no lesion on MRI would miss up to 5-11% of all csPCa cases (ISUP grade >2) [5,8], whereas performing biopsy in all patients with an equivocal MRI finding (PI-RADS 3 lesions considered to be positive by guidelines [9]) can result in a diagnosis of csPCa in 3-50% of the patients [5,8,10,11]. In this scenario, prostate-specific antigen (PSA) density (PSAd) is one of the strongest predictors of csPCa in risk models, and several studies found that PSAd and prostate MRI suspicion score, such as the PI-RADS score or Likert score, were significant independent predictors of csPCa at biopsy [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Dies zieht eine Übertherapie nach sich. Die qualitative multiparametrische MRT mit anschließender MR-gestützter Biopsie ist der TRUS-Biopsie diesbezüglich deutlich überlegen [1]. Dies gilt insbesondere bei anterior, apikal und lateral gelegenen Tumoren.…”
Section: Einführungunclassified